If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v * v + 7 * 7 = 2v * 2v + 17v + 45 Multiply v * v v2 + 7 * 7 = 2v * 2v + 17v + 45 Multiply 7 * 7 v2 + 49 = 2v * 2v + 17v + 45 Reorder the terms: 49 + v2 = 2v * 2v + 17v + 45 Reorder the terms for easier multiplication: 49 + v2 = 2 * 2v * v + 17v + 45 Multiply 2 * 2 49 + v2 = 4v * v + 17v + 45 Multiply v * v 49 + v2 = 4v2 + 17v + 45 Reorder the terms: 49 + v2 = 45 + 17v + 4v2 Solving 49 + v2 = 45 + 17v + 4v2 Solving for variable 'v'. Reorder the terms: 49 + -45 + -17v + v2 + -4v2 = 45 + 17v + 4v2 + -45 + -17v + -4v2 Combine like terms: 49 + -45 = 4 4 + -17v + v2 + -4v2 = 45 + 17v + 4v2 + -45 + -17v + -4v2 Combine like terms: v2 + -4v2 = -3v2 4 + -17v + -3v2 = 45 + 17v + 4v2 + -45 + -17v + -4v2 Reorder the terms: 4 + -17v + -3v2 = 45 + -45 + 17v + -17v + 4v2 + -4v2 Combine like terms: 45 + -45 = 0 4 + -17v + -3v2 = 0 + 17v + -17v + 4v2 + -4v2 4 + -17v + -3v2 = 17v + -17v + 4v2 + -4v2 Combine like terms: 17v + -17v = 0 4 + -17v + -3v2 = 0 + 4v2 + -4v2 4 + -17v + -3v2 = 4v2 + -4v2 Combine like terms: 4v2 + -4v2 = 0 4 + -17v + -3v2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. -1.333333333 + 5.666666667v + v2 = 0 Move the constant term to the right: Add '1.333333333' to each side of the equation. -1.333333333 + 5.666666667v + 1.333333333 + v2 = 0 + 1.333333333 Reorder the terms: -1.333333333 + 1.333333333 + 5.666666667v + v2 = 0 + 1.333333333 Combine like terms: -1.333333333 + 1.333333333 = 0.000000000 0.000000000 + 5.666666667v + v2 = 0 + 1.333333333 5.666666667v + v2 = 0 + 1.333333333 Combine like terms: 0 + 1.333333333 = 1.333333333 5.666666667v + v2 = 1.333333333 The v term is 5.666666667v. Take half its coefficient (2.833333334). Square it (8.027777782) and add it to both sides. Add '8.027777782' to each side of the equation. 5.666666667v + 8.027777782 + v2 = 1.333333333 + 8.027777782 Reorder the terms: 8.027777782 + 5.666666667v + v2 = 1.333333333 + 8.027777782 Combine like terms: 1.333333333 + 8.027777782 = 9.361111115 8.027777782 + 5.666666667v + v2 = 9.361111115 Factor a perfect square on the left side: (v + 2.833333334)(v + 2.833333334) = 9.361111115 Calculate the square root of the right side: 3.059593292 Break this problem into two subproblems by setting (v + 2.833333334) equal to 3.059593292 and -3.059593292.Subproblem 1
v + 2.833333334 = 3.059593292 Simplifying v + 2.833333334 = 3.059593292 Reorder the terms: 2.833333334 + v = 3.059593292 Solving 2.833333334 + v = 3.059593292 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2.833333334' to each side of the equation. 2.833333334 + -2.833333334 + v = 3.059593292 + -2.833333334 Combine like terms: 2.833333334 + -2.833333334 = 0.000000000 0.000000000 + v = 3.059593292 + -2.833333334 v = 3.059593292 + -2.833333334 Combine like terms: 3.059593292 + -2.833333334 = 0.226259958 v = 0.226259958 Simplifying v = 0.226259958Subproblem 2
v + 2.833333334 = -3.059593292 Simplifying v + 2.833333334 = -3.059593292 Reorder the terms: 2.833333334 + v = -3.059593292 Solving 2.833333334 + v = -3.059593292 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2.833333334' to each side of the equation. 2.833333334 + -2.833333334 + v = -3.059593292 + -2.833333334 Combine like terms: 2.833333334 + -2.833333334 = 0.000000000 0.000000000 + v = -3.059593292 + -2.833333334 v = -3.059593292 + -2.833333334 Combine like terms: -3.059593292 + -2.833333334 = -5.892926626 v = -5.892926626 Simplifying v = -5.892926626Solution
The solution to the problem is based on the solutions from the subproblems. v = {0.226259958, -5.892926626}
| A+2=b-4 | | (2/3)=18 | | x-(-20)=104 | | y=100-(120-x) | | y=100-(100-x) | | x+(-5)=-7 | | 4c^3+8c=0 | | u*u+6u-7=0 | | u*u+6u=7 | | u*u*u+6u=7 | | 180-x+5x=460-5x+5x | | 10x+5y+0.05z=100 | | -x^3+6*x^2=-13x+42 | | 8r^2+2=114 | | x=2-1+2(4)-3(5)+23-12-12+23(2) | | x=2-1+2(4)-3(5)+23-12-1/2 | | x=2-1+2(4)-3(5)+23-12-1/3 | | x=2-1+2(4)-3(5)+23-12-1 | | x=2+24+123-56+23 | | x^2(x+5)=144 | | 50x=30(x+2) | | 5ysquared+18y+7=0 | | 5y+18y+7=0 | | x+x+1=1.10 | | x=15+3*-4 | | 3(15+3y)+2y=1 | | 2+4-6*2+2*5+6=10 | | 1.0-3.7x=-4.2x+0.3 | | 3.57x+1.61=4.71 | | 4y-3=80 | | -7+10=-20 | | x^3+10x+k=0 |